2016
DOI: 10.1039/c5cy01437a
|View full text |Cite
|
Sign up to set email alerts
|

Metal-supported carbon-based materials: opportunities and challenges in the synthesis of valuable products

Abstract: We summarize relevant applications and limitations of metal-supported carbons and nanocarbons in the synthesis of valuable products and the recent advances in this field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
80
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 153 publications
(81 citation statements)
references
References 234 publications
0
80
0
1
Order By: Relevance
“…These energies were assigned to the Cl-Pd bonding energy from the oxime palladacycle 1. The band at 200.1 8 eV corresponded to the 2p3/2 aromatic-Cl bonding energy (Figure 3e) [62]. Thus, performing the palladation reaction using THF as solvent before immobilization onto GO led to the integral cyclopalladated species being supported.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…These energies were assigned to the Cl-Pd bonding energy from the oxime palladacycle 1. The band at 200.1 8 eV corresponded to the 2p3/2 aromatic-Cl bonding energy (Figure 3e) [62]. Thus, performing the palladation reaction using THF as solvent before immobilization onto GO led to the integral cyclopalladated species being supported.…”
Section: Resultsmentioning
confidence: 99%
“…Catalysts 2017, 7, 94 2 of 16 of palladacycles to graphene materials, with two studies having been reported so far using covalent immobilization strategies [62,63]. Very recently, we have shown that palladium nanoparticles (Pd NPs), supported on graphene and reduced graphene oxide, efficiently catalyze the Suzuki-Miyaura coupling between aryl bromides and potassium aryltrifluoroborates under aqueous and low loading conditions (0.1 mol % Pd) employing conventional or microwave heating [64].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations